New species and additional records of Lathrobium and Elytrobium from the Palaearctic region, with special reference to the fauna of East Yunnan (Coleoptera: Staphylinidae: Paederinae). - Assing, Volker (Contributions to Entomology = Beiträge zur Entomologie, 2015)
Seventeen species of Lathrobium Gravenhorst, 1802 and one of Elytrobium Assing, 2013 are (re-)described and illustrated: Lathrobium struyvei spec. nov. (Spain), a close relative of L. dimidiatipenne Bernhauer, 1910; L. kiruense spec. nov. (Nepal: Annapurna) of the L. emodense group; L. undosum spec. nov. (Nepal: Solu Khumbu), tentatively assigned to the L. discissum group; L. crenatum spec. nov. (China: East Yunnan), L. rostratum spec. nov. (China: East Yunnan), L. tricarinatum spec. nov. (China: East Yunnan), and L. laciniatum spec. nov. (China: East Yunnan), all four of them of the L. tentaculatum group; L. daweianum spec. nov. (China: Southeast Yunnan) of the newly established L. daweianum group; L. coadultum spec. nov. (China: Southeast Yunnan) of the newly established L. coadultum group; L. grebennikovi spec. nov. (China: Shaanxi: Qinling Shan) and L. cavisulcatum spec. nov. (China: Shaanxi: Qinling Shan) of the L. varisternale group; L. abruptum spec. nov. (China: Sichuan: Gongga Shan), a close relative of L. hailuogouense Peng et al., 2012; L. erectum spec. nov. (China: Guizhou: Fanjing Shan) of the L. fissispinosum group; L. scaphiforme spec. nov. (Japan: Honshu); L. volutum spec. nov. (Japan: Honshu); L. trabale spec. nov. (Japan: Honshu); L. oharai Watanabe, 2014; Elytrobium edentulum spec. nov. (China: Shaanxi: Qinling Shan). The diversity, biogeography, natural history, and phylogenetic affiliations of the Lathrobium fauna of East Yunnan, from where the genus is reported for the first time, are discussed. The general distribution of Lathrobium and the individual distributions of the newly described species in Yunnan are mapped. Additional records of 30 described and one unnamed Lathrobium species are reported from Middle Asia (one species), Nepal (five species), from the Chinese provinces Yunnan (five species), Sichuan (five species), Shaanxi (one species), and Guizhou (one species), from Taiwan (one species), and from Japan (13 species). Three of these species are reported from Japan for the first time. Additional records of two Elytrobium species are reported from China and Japan. Lathrobium is now represented in the Palaearctic region by 563 species and ten subspecies, in China by 206 species (67 of which are confined to Yunnan), in Japan by 114, and in the Himalaya by 70 species. Elytrobium currently includes a total of seven species distributed in China, Taiwan, and Japan. Keywords Coleoptera, Staphylinidae, Paederinae, Lathrobiina, Lathrobium, Elytrobium, Palaearctic region, China, Yunnan, taxonomy, new species, species groups, sexual size dimorphism, diversity, distribution maps, new records. Nomenclatural Acts edentulum Assing, 2015 (Elytrobium), spec. n. abruptum Assing, 2015 (Lathrobium), spec. n. calvisulcatum Assing, 2015 (Lathrobium), spec. n. coadultum Assing, 2015 (Lathrobium), spec. n. crenatum Assing, 2015 (Lathrobium), spec. n. daweianum Assing, 2015 (Lathrobium), spec. n. erectum Assing, 2015 (Lathrobium), spec. n. grebennikovi Assing, 2015 (Lathrobium), spec. n. kiruense Assing, 2015 (Lathrobium), spec. n. laciniatum Assing, 2015 (Lathrobium), spec. n. rostratum Assing, 2015 (Lathrobium), spec. n. scaphiforme Assing, 2015 (Lathrobium), spec. n. struyvei Assing, 2015 (Lathrobium), spec. n. trabale Assing, 2015 (Lathrobium), spec. n. tricarinatum Assing, 2015 (Lathrobium), spec. n. undosum Assing, 2015 (Lathrobium), spec. n. volutum Assing, 2015 (Lathrobium), spec. n.